2016
DOI: 10.1523/jneurosci.1038-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Store-Operated Calcium Entry Leads to Striatal Synaptic Loss in a Huntington's Disease Mouse Model

Abstract: In Huntington's disease (HD), mutant Huntingtin (mHtt) protein causes striatal neuron dysfunction, synaptic loss, and eventual neurodegeneration. To understand the mechanisms responsible for synaptic loss in HD, we developed a corticostriatal coculture model that features age-dependent dendritic spine loss in striatal medium spiny neurons (MSNs) from YAC128 transgenic HD mice. Age-dependent spine loss was also observed in vivo in YAC128 MSNs. To understand the causes of spine loss in YAC128 MSNs, we performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
209
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(229 citation statements)
references
References 62 publications
16
209
3
Order By: Relevance
“…These data also supports potential use of IC10 peptide as a novel HD therapeutic agent [79]. In further experiments, it was shown that chronically enhanced calcium leakage from YAC128 MSN ER caused a reduction in the ER calcium level and led to increased stromal interaction molecule 2-mediated store-operated calcium entry, and that resulted in the MSN spine loss both in vitro and in vivo [80].…”
Section: Huntington's Diseasesupporting
confidence: 67%
“…These data also supports potential use of IC10 peptide as a novel HD therapeutic agent [79]. In further experiments, it was shown that chronically enhanced calcium leakage from YAC128 MSN ER caused a reduction in the ER calcium level and led to increased stromal interaction molecule 2-mediated store-operated calcium entry, and that resulted in the MSN spine loss both in vitro and in vivo [80].…”
Section: Huntington's Diseasesupporting
confidence: 67%
“…Mutant HTT (mHTT) has been shown to disrupt a number of cellular and molecular processes that are thought to contribute collectively to clinical manifestations of the disease. These include transcriptional dysfunction (1,2), deficits in trophic support (2)(3)(4), and imbalances in neurotransmitter levels and signaling (5,6) as well as aberrant calcium handling by synaptic (7,8), ER (7,8), and mitochondrial pathways (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, however, reported SOCE responses in dendritic spines 8,9 , small dendritic protrusions at the tip of which terminate most excitatory inputs. Synaptic SOCE is STIM2-dependent, has been linked to spine maturation and is dysregulated in mouse models of Alzheimer's and Huntington's disease [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%